B-cell engineering: A promising approach towards vaccine development for COVID-19 (2020)
With the number of cases crossing six million (and more than three hundred and seventy thousand deaths) worldwide, there is a dire need of a vaccine (and repurposing of drugs) for SARS-CoV-2 disease (COVID-19). It can be argued that a vaccine may be the most efficient way to contain the spread of this disease and prevent its future onset. While many attempts are being made to design and develop a vaccine for SARS-CoV-2, pertinent technological hitches do exist. That is perhaps one of the reasons that we don’t have vaccine for coronaviruses (including SARS-CoV-1 and MERS). Recently developed CRISPR-mediated genome editing approach can be repurposed into a cell-modification endeavor in addition to (and rather than) correcting defective parts of genome. With this premise, B-cells can be engineered into universal donor, antigen specific, perpetually viable, long lasting, non-oncogenic, relatively benign, antibody producing cells which may serve as an effective vaccine for SARS-CoV-2 and, by the same rationale, other viruses and pathogens.